2015
DOI: 10.1051/epjconf/20159401008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on dynamic splitting of recycled concrete using SHPB

Abstract: Abstract. To study the recycled concrete splitting tensile properties and fracture state with various recycled coarse aggregate replacement percentage (i.e. 0%, 25%, 50%, 75% and 100%), the dynamic splitting test of recycled concrete was carried out using large diameter (75 mm) split Hopkinson pressure bar (SHPB). The results show that the recycled concrete splitting tensile strength increases with the increase of loading rate, and the loading rate also affects the recycled concrete fracture state, which indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The position of the specimen is shown in the Fig.1. This arrangement, which is known as the Brazilian test, or diametric compression test, is a typical indirect tensile test, which was developed to determine the tensile strength of brittle materials such as rock, ceramics and concrete [3][4][5][6]. Even this method was developed for the study of the fracture behaviour at quasi-static loading, numerical analysis, Antoun et al [7] found that the stress distribution in the dynamic Brazilian test was similar to the static test; therefore, they thought that the dynamic Brazilian test was an effective method to measure the tensile properties.…”
Section: Materials and Experimental Techniquementioning
confidence: 99%
“…The position of the specimen is shown in the Fig.1. This arrangement, which is known as the Brazilian test, or diametric compression test, is a typical indirect tensile test, which was developed to determine the tensile strength of brittle materials such as rock, ceramics and concrete [3][4][5][6]. Even this method was developed for the study of the fracture behaviour at quasi-static loading, numerical analysis, Antoun et al [7] found that the stress distribution in the dynamic Brazilian test was similar to the static test; therefore, they thought that the dynamic Brazilian test was an effective method to measure the tensile properties.…”
Section: Materials and Experimental Techniquementioning
confidence: 99%